Number 13 / Part I. Music. 3. Mad Scenes: A Warning against Overwhelming Passions - Marisi Rossella (Sciendo, 2017)
This study focuses on mad scenes in poetry and musical theatre, stressing that, according to Aristotle's theory on catharsis and the Affektenlehre, they had a pedagogical role on the audience. Some mad scenes by J.S. Bach, Handel and Mozart are briefly analyzed, highlighting their most relevant textual and musical characteristics.